Changes in body composition of Wistar rats: effects of high-intensity interval training (Bioscience Journal, 2023)
The present study aimed to investigate the effectiveness of high-intensity interval training (HIIT) in the body composition of Wistar rats. The HIIT protocol consisted of high-intensity swimming three times a week for four weeks. There were no differences between groups as to the Lee index. However, the weights of the perigonadal (p=0.001) and retroperitoneal (p=0.026) fats were significantly different between the Control Group (CG, n=10) vs. Trained Group (TG, n=10), respectively. There was also a significant increase in the body weight of the animals in TG (16.43%) and CG (7.19%) at the end of the experiment. These findings suggested that HIIT was not sufficient to improve significantly the body composition of rats.